(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2021)
The Balu River is a peripheral river of Dhaka Metropolis and like other rivers its water quality is also highly vulnerable towards pollution. In the present study, effects of water quality parameters on the phytoplankton biomass have been studied for six climatic seasons of the year. The results obtained were compared with two other rivers of Dhaka Metropolis namely, Buriganga and Turag. Balu River showed water quality characters almost comparable with two other rivers. The phytoplankton biomass as chlorophyll a (chl-a) was found to be correlated directly with air and water temperature and alkalinity of the water. However, a weak positive correlation was obtained between chl-a and Secchi depth and free CO2 concentration. Nitrate nitrogen showed weak negative correlation with chl-a and phaeopigment and phytoplankton total density. High fluctuation was observed in the concentration of DO (0.20 - 4.50 mg/l) and free CO2 (0.06 - 2.90 mg/l) throughout the seasons. Soluble reactive phosphorus ranged from 30 - 1248 μg/l and chl-a ranged from 6.77 - 32.60 μg/l. Phytoplankton density ranged 1178 - 7409×103 ind./l over the study year. Water color ranged from light blue to dark black. The depth of visibility as Secchi depth varied from 15.24 - 81.28 cm whilst the water depth of the studied station Paschim Gaon of Balu River ranged from 4.57 - 7.92 m. Air and water temperature ranged from 25.4 - 36.5°C and 23.4 - 32.3°C, respectively. J. Biodivers. Conserv. Bioresour. Manag. 2020, 6(1): 37-46